Long non‐coding RNA HULC protects against atherosclerosis via inhibition of PI3K/AKT signaling pathway. Issue 1 (7th December 2020) - Mu, Dan; Li, Danyan; Li, Jianhui; Yu, Hongming; Chen, Wenping; Liang, Jing; Wang, Dongmei; Li, Aimei; Qing, Zhao; Zhang, Bing
Abstract: Studies on the roles of long non‐coding RNA in atherosclerosis (AS) have been extensively explored. However, the action of lncRNA highly upregulated in liver cancer (HULC) in AS still needs in‐depth investigations. Hence, this study is launched towards the translation of HULC‐oriented mechanism in AS. Mouse AS models were established by high cholesterol and high fat feeding. AS mice were injected with restored HULC or phosphatidylinositide 3‐kinase/protein kinase B (PI3K/AKT) signaling pathway inhibitor to explore their roles in AS. Blood lipid, inflammation and oxidative stress were detected as well as HULC, PI3K, phosphated‐PI3K (p‐PI3K), AKT, p‐AKT, and aortic vascular cell apoptosis were determined. HULC was poorly expressed, p‐PI3K and p‐AKT were highly expressed in AS. HULC inhibited the PI3K/AKT signaling pathway. In AS, by inhibition of PI3K/AKT signaling pathway, restored HULC restrained atherosclerotic plaque formation, alleviated aortic intimal damage and reduced collagen fiber content in aorta, down‐regulated blood lipid levels, and inhibited inflammation, oxidative stress and aortic vascular cell apoptosis. Our study elucidates that HULC alleviates AS via inhibition of the PI3K/AKT signaling pathway, which provides a potential biomarker for treatment of AS.